Online Tutorial And Webinar Tutorial Management On Distence Learning Process At Indonesia Open University - Budiarso, Iwan; Suhendraya Muchtar, Hendi; H Soro, Suharyanto; Mardiana, Dinny (International Journal of Educational Research & Social Sciences, 2022)
The Open University provides study assistance services to students in the form of a Tutorial program. The implementation of the Tutorial managed by the Tutor as a facilitator has not run optimally. This situation becomes the background of the research problem. The purpose of this research is to analyze the management of Tuton and Tuweb tutors. The theory used is in the form of management functions initiated by Terry. This research is a descriptive study with a qualitative approach that reveals the situation by describing the reality correctly and naturally in the distance learning procession. Data was collected through observation, interviews, documentation, and triangulation. The data obtained were then reduced, presented, and concluded. The results of the research generally reveal that management functions have been carried out but their implementation has not been fully implemented. Specific conclusions show (1) Planning: carrying out tutorial preparation meetings and tutor evaluations. (2) Organizing: determine the standardization of Tutors, standardization of recruitment, employment contracts, letters of assignment, and decrees for Tutors Tutons, and letters of assignments for Tutors Tuwebs. (3) Mobilization: organizing Tutor training and refreshment, Whatsapp Group communication, providing reminders and motivation, (4). Controlling: Tuton tutors do not have a routine control schedule yet. Tuweb tutors have a regular control schedule. (5) There are obstacles and solutions as well as future improvements. From these general and specific conclusions, the researcher recommends the Tutor management model to maximize the Tutor management which will have implications for improving the Tutor's performance in managing the Tutorial class.